Listening an automaton ear: aesthetics and eroticism of ASMR: estética e erotismo do ASMR - Martini, Felipe (2021)
From a brief analysis of two ASMR videos (Autonomous Sensory Meridian Response), available on the social network youtube, the author proposes an essay about contemporary listening. The ASMR subculture and the tingly aesthetics are presented as emerging modes of audiovisual consumption in dialogue with the notions of anesthetics, by Walter Benjamin and eroticism by George Bataille. The resulting hypothesis is the emergence of an automatic erotic and aesthetic realization, result of the human relationship in sociotechnical networks, which enhances the alienation of sleep by the late capitalism.